Effect of sterol regulatory element binding protein 1c expression on intestinal gluconeogenesis in mice - ZHANG Linlin; XIAO Yuxi; LIU Bingyao (陆军军医大学学报, 2024)
Objective To investigate the regulation role of sterol regulatory element binding protein 1c (SREBP1c) in intestinal gluconeogenesis. Methods After C57BL/6 mice, and SREBP1c homozygous knockout (SREBP1c-KO) and littermate wild-type (SREBP1c-WT) mice were fasted for 48 h, qPCR and Western blotting were used to detect the expression of rate-limiting gluconeogenic genes glucose-6-phosphatase (G6PC) and phosphoenolpyruvate carboxykinase 1 (PCK1) in the liver, jejunum and ileum tissues at mRNA and protein levels. After overexpression or knockdown of SREBP1c in the intestinal epithelial cell line CaCo-2, the expression levels of G6PC and PCK1 were measured. Results The expression levels of G6PC, PCK1, and SREBP1c were significantly increased in the jejunum and ileum tissues of C57BL/6 mice after fasting (P < 0.05). In SREBP1c-KO mice, fasting treatment induced obviously inhibited expression of G6PC and PCK1 in the jejunum and ileum tissues (P < 0.05). Overexpression of SREBP1c significantly upregulated the expression levels of G6PC and PCK1, and promoted the production of glucose in CaCo-2 cells (P < 0.05). Conversely, knocking SREBP1c down resulted in down-regulation of G6PC and PCK1 and suppressed production of glucose in CaCo-2 cells (P < 0.05). Conclusion Under fasting, SREBP1c is involved in regulation of G6PC and PCK1 in intestinal epithelial cells, and thus affects glucose production. It indicates that SREBP1c might be involved in the regulation of intestinal gluconeogenesis, and the mechanism needs further exploration.